Occludin degradation makes brain microvascular endothelial cells more vulnerable to reperfusion injury in vitro. Issue 3 (7th July 2020) - Zhang, Yuan; Li, Xiaofeng; Qiao, Shanshan; Yang, Dexin; Li, Zongyang; Xu, Ji; Li, Weiping; Su, Li; Liu, Wenlan
Abstract: Intracerebral hemorrhage is the most dangerous complication in tPA thrombolytic therapy for ischemic stroke, which occurs as a consequence of endothelial cell death at the blood–brain barrier (BBB) during thrombolytic reperfusion. We have previously shown that cerebral ischemia‐induced rapid occludin degradation and BBB disruption. Here we demonstrated an important role of occludin degradation in facilitating the evolution of ischemic endothelial cells toward death. Cultured brain microvascular endothelial cells (bEnd.3 cells) were exposed to oxygen‐glucose deprivation (OGD) or incubated with occludin siRNA or occludin AAV to achieve an occludin deficiency or over‐expression status before exposing to reoxygenation (R) or TNF‐α treatment. Cell death was assessed by measuring lactate dehydrogenase release, TUNEL staining, and flow cytometry analysis. Inhibition of OGD‐induced occludin degradation with SB‐3CT or over‐expression of occludin with occludin AAV both significantly attenuated OGD/R‐induced apoptosis and pyroptosis in bEnd.3 cells. Consistently, knockdown of occludin with siRNA potentiated TNF‐α‐induced apoptosis, supporting an important role of occludin integrity in endothelial cell survival. Similar results were observed for pyroptosis, in which occludin knockdown with siRNA led to a significant augmentation of cytokines secretion, inflammasome activation, and pyroptosis occurrence in TNF‐α‐treated bEnd.3 cells. Lastly, up‐regulation of c‐Yes, PI3K/AKT, and ERK concurrently occurred with occludin degradation after OGD/R or TNF‐α treatment, and the level of these proteins were further increased when inhibition of occludin degradation or over‐expression of occludin. These data indicate that occludin degradation inflicted during ischemia makes BBB endothelial cells more vulnerable to reperfusion‐associated stress stimuli. Abstract : We aimed to explore an important role of occludin degradation in facilitating the evolution of ischemic endothelial cells toward death. Brain microvascular endothelial cells were exposed to oxygen‐glucose deprivation/reperfusion (OGD/R) or TNF‐α treatment. The findings are as follows: 1) inhibiting occludin degradation alleviates OGD/R‐induced cell apoptosis and pyroptosis; 2) knockdown of occludin aggravates TNF‐α‐induced apoptosis and pyroptosis, whereas over‐expression of occludin reverses these effect; 3) up‐regulation of c‐Yes, PI3K/AKT, and ERK concurrently occurred with occludin degradation after OGD/R or TNF‐α treatment, and the level of these proteins were further increased when inhibition of occludin degradation or over‐expression of occludin.